Sosialisasi Prosedur Sertifikasi Halal Bagi Pelaku Usaha dan Masyarakat di Desa Lokasi Baru - Agusti, Netta; Yuliarti, Ellys (Jurnal Pengabdian Kepada Masyarakat, 2024)
The halal issue is a major problem and can influence consumer perceptions about a product, especially Muslim consumers. When consuming food products, halal provisions are a priority. The halal concept requires that food products are nutritious and made from permitted, clean and hygienic ingredients. This can be seen from the large demand for halal food with halal certificates/logos throughout the world so that halal labeling on product packaging is considered important in protecting consumers, especially Muslim consumers. Participants were very enthusiastic about taking part in the socialization series. Public understanding of the importance of halal certification and labeling has also increased, thereby providing benefits to socialization participants. This activity has had a good influence on business people in Lokasi Baru Village. This activity can increase their understanding, knowledge and awareness regarding the importance of halal standards for a product in order to increase sales, so that in the end it can increase the income of the people of Lokasi Baru Village.